Identifying Awareness, Use, and Perceptions of text4baby among Family Medicine and Obstetrics and Gynecology Practitioners at the University of Kansas Medical Center - Bjornsen, Brent; McHaney, Mark; Merando, Katie; Tusken, Cameron; Befort, Christie; Cain, Cristi; Shaw, Pam (Kansas Journal of Medicine, 2014)
Background. Low income minority women who receive inadequate or no prenatal care have greater infant morbidity and mortality in the postnatal period. Mobile health or mHealth initiatives such as text4baby are presumed to be a means to reach underserved pregnant and postpartum women to increase their use of prenatal and postnatal care. Providers are an important referral source for mHealth initiatives. It is important, therefore, to assess the awareness, use, and perceptions of the text4baby program among Family Medicine and Obstetrics/Gynecology (Ob/Gyn) providers to determine the means to increase referrals and improve outcomes for pregnant mothers and infants. Methods. Family medicine and Ob/Gyn providers (attending physicians, residents, nurse practitioners, nurses, and medical assistants) at the University of Kansas Medical Center (KUMC) completed a survey assessing awareness of use and perceived utility of text4baby as well as experience with technology and reservations about mHealth in general. Results. Seventy-eight providers (38 in Family Medicine and 40 in Ob/Gyn) responded to the survey. Awareness of text4baby among all providers was 18%. Among the 14 providers who knew about text4baby, one individual stated he/she regularly refers patients to text4baby and 11 agreed that text4baby is a useful tool for the care of pregnant patients. Comparison of text4baby awareness by demographic factors showed no significant differences between any of the groups. Providers who knew of mHealth applications were more likely to know about text4baby (p = 0.04). Older providers were less likely to have reservations about using mHealth in their practice (p = 0.02). There was widespread agreement (87%) that providing evidence to clinicians that text4baby improves outcomes would increase use of the service in clinical practice. Conclusions. Awareness of text4baby among practitioners at KUMC is minimal; use is negligible. Our study identified lack of awareness of the text4baby service and of supporting evidence about its effectiveness as the primary barriers to referral.